Detection of antibodies against bluetongue virus in sheep from two locations in Junín, Peru - Jurado P., Jessica (2020)
The aim of this study was to detect antibodies against bluetongue virus (VLA) in a population of Junín breed sheep bred at 3800 m above the see level in the province of Jauja, Junín and in Blackbelly breed sheep raised at 600 m in the province of Chanchamayo, Junín, Peru. Blood samples (n=306) were collected from Junín sheep, older than 4 months of age, both sexes and from Blackbelly sheep (n=82) older than 4 months, both sexes, from small breeders from four districts (Perene, San Luis de Shauro, San Ramón and Pichanaki) from the province of Chanchamayo, Junín. Antibody detection against the VLA was done by competition ELISA test. All samples (306/306) of the Junín sheep were negative for antibodies against the VLA, while 56.1% (46/82) of the Blackbelly sheep samples had antibodies against the virus. The absence of antibodies against the VLA in sheep raised at 3800 m of altitude indicates that they were not exposed to the VLA, suggesting that high altitude and low temperatures constitute a barrier to the biology of the virus-transmitting vectors, whereas sheep raised at 600 m of altitude were exposed, indicating the presence of the vector or vectors competent for the transmission of bluetongue virus.